The social climber - Pellegrino, Amanda (Park Row Books, 2023)
"It's the week before her wedding, and all of Eliza's meticulous planning is about to pay off. She's become the exact type of woman who would marry into the prominent blue-blooded Walker family--Ivy League credentials, a high-powered PR job and a designer-label wardrobe. But as the big day approaches, secrets from Eliza's past attendance at an Evangelical college start to throw her true motives into question. Who exactly is Eliza Bennet and what does she really want?" --